Leg Muscle Power, Speed, and Flexibility Correlate with Mawashi Geri Chudan Kicking Performance in 12-14-Year-Old Boys at Dojo Victori's Karate - Joel Simarmata; Mahmuddin Mahmuddin (Journal of Indonesian Active in Sports, 2024)
The purpose of this research is to know the relationship between legs muscles™ power, speed, and flexibility with mawashi geri chudan kicking toward boys Dojo Victori™s Karate athletes aged 12-14 years in 2022. The research method used is quantitative research through an experimental approach. Sampling technique in this research is purposive sampling with some requirements for population of boys™ Dojo Victori. This research is held starting from October 26th to November 16th, 2022. Statistical results show that legs muscle power is significantly related to the mawashi geri chudan kicking of 40.96%; leg muscle speed is significantly related to the mawashi gery chudan kicking of 56.25%; and leg muscle flexibility is significantly related to the mawashi gery chudan kicking of 72.25%. Subsequent statistical tests on all components have a simultaneously and significantly relationship to the kicking technique of 75.69%. Thus, the research will provide insight and knowledge for karate coaches to pay attention to the physical fitness components of their athletes, such as power, speed, and flexibility in the leg muscles. In addition, it is needed for further research on other components of physical fitness so that coaches get a complete and comprehensive understanding for the development of their athlete's abilities.